Performance Test of Axial Turbine-Generator Magnet Permanent On-Grid System Prototipe for Very Low Head Application - Abdul Ghaniy (NIM: 23114308), Dhani
Many rivers which have large flow rate but low head, and Irrigation canals scattered throughout Indonesia are New and Renewable Energi (NRE) potentials whose the utilization is still very low. To promote and develop NRE utilization as power plant, the government has issued policy that allows the NRE power plant connect to the grid. This study is aims to investigate kinerjance of On-Grid hydro power plant sistem prototype that utilize very low head potential (<1 m). The protype sistem consist of Axial Hydro Turbine Permanent Magnet Generator (TAGMP) designed to operate at speed 90 rpm, flow rate 128 litre/second and head only 30 cm, generating AC electric power 300W at 220V 50Hz, connected to automatic voltage stabilizer to maintain the voltage at 220V. The AC power converted to DC power by diode rectifier with π filter to minimize DC voltage ripple, next connected to Grid Tie Inverter (GTI) which has MPPT to inject maximum AC power to the grid. The TAGMP is placed on an open water canal with cross section dimension 84x115 cm. and the test was performed on variations of flow rate 0.199 m3 / s, 0.246 m3 / s, 0.270 m3 / s, 0.291 m3 / s, 0.304 m3 / sand 0.326 m3 / s to know the characteristics of AC power TAGMP, DC power before connected to the grid and power injected the On-Grid sistem to the grid. The highest efficiency of the On-Grid sistem is 4.71% with maximum power supplied to the PLN grid is 37.37W, was achieved at a flow rate of 0,270 m3 / s , head 30 cm, and the efficiency of TAGMP, STAVOLT, Rectifier and GTI are 8,91%, 97,5%, 94,52% and 57,38% respectively. The small efficiency of the sistem was caused by decreasing Permanent Magnet Generator (PMG) performance on TAGMP if compared to test results when TAGMP was new. In order to troubleshoot a decline in PMG performance, the inner casing material of the PMG stator was changed from ST37 to PVC then tested using an electric motor as a prime mover connected to PMG by 2 belt transmissions and 1 gearbox. Test results, the PMG kinerjance not yet recovered. At 50Hz of PMG voltage frequency, the terminal voltage drops from 453.5V at no load condition to 104V at current 2.41A. Nevertheless, there was an increase in power generated by PMG 478.85W at a voltage 305V and current 1.57A. Measurement of the isolation resistance in the PMG stator coils was done and the measurement results indicate there is insulation leakage. Based on the visual inspection to the coil, was found that there is a scratched wire and attached to the iron core and there are some coils whose the wire has started to flaw. Rewinding on all PMG stator coils was done with some modifications of changing the diameter of winding wire from 0.9 mm to 1mm, making cartridge for the coil and change the coil to coil joint from the solder joints to the clamp joints to avoid damage to wire enamel due to heat during soldering . The result of PMG testing after rewinding at 50 Hz voltage frequency is the terminal voltage drops from 402V at no load condition to 97.09V at 2.45A current. The maximum electric power generated is 425.1W at voltage 271.8V and current 1.56A. If compared with GMP test results of PVC casing before rewinding, it does not show any improvement in performance. By using electric motor prime mover, 2 belt and 1 gearbox as transmissions, On-Grid sistem consist of PMG-STAVOLT-Rectifier-GTI was tested at PMG voltage frequency 30Hz, 40Hz and 50Hz. The results are the maximum power supplied by the sistem to PLN in each GMP frequency variation are 135,6W, 236,7W and 313W, the sistem efficiency are 17,7%, 25,4% and 29,7% respectively. At 50Hz frequency testing, the STAVOLT is trip couse by the STAVOLT input voltage exceeds the maximum limit. The On-Grid sistem consist of PMG-Rectifier-GTI, without STAVOLT, at PMG frequency 30Hz, 40Hz and 50Hz was tested also. As a result, the maximum power supplied by the sistem to PLN at each frequency variation is 169.4W, 245W and 325W with the sistem efficiency of 22.1%, 26.2% and 30.6% respectively.